Cellulose-based halochromic sensor for real-time surveillance of spoilage of packed fish - Kesavan Devarayan; Gangeswar Mohan; Yazhiniyan Palanisamy; Anand Theivasigamani; Evon Umesh Siluvai John; Monikandon Sukumaran; Hema Anjappan (Discover Food)
Abstract The development of a biopolymer-based color-changing visual sensor for monitoring the spoilage of fishery products is described in this study. At first, a cellulose-based composite film containing mixed-indicator dyes was fabricated. The film was characterized using UV–visible and FT-IR spectroscopy, scanning electron microscopy, thermogravimetric analysis, lab, and RGB measurements. The halochromic properties of the film were evaluated through ammonia test and colorimetry. The developed film sensor is tested for monitoring the spoilage of packed seer fish fillets at room temperature for up to 48 h and at 4 °C for up to 10 days. The sensor displayed distinct color changes correlating with the spoilage of the packed fish. Analysis of total volatile basic nitrogen and pH levels of the samples revealed a correlation between the halochromism of the sensor and the spoilage of the fish. The color-changing pattern of the sensor was consistent with the results of microbial analysis. The present study reveals a promising material combination for fabricating simple visual sensors from biomaterials, which can be used to monitor the real-time deterioration of packaged fishery products.